Testicular lymphoma in inguinal hernia - Olivares, Eduardo Poblano; Olmos Gonzalez, Jorge L. (International Journal of Research in Medical Sciences, 2021)
Primary testicular lymphoma is a rare disease that has a higher incidence in patients over 60 years of age, presenting as an increase in volume in the inguinal region, which is usually painless and slow-growing. In the case that we present, it is a patient who was initially diagnosed with an indirect inguinal hernia due to the findings on examination and ultrasound, without presenting relevant findings in the laboratory studies, during the trans-operative we found testicular tumor compatible with diffuse large B-cell lymphoma, this being the most common variant of testicular lymphoma. This case emphasizes on importance of pre-operative suspicion in older age patients with increased volume in the groin region and without a clear diagnosis.